CONCEPT AND DESIGN BASIC TRAINING AS AN INFORMATION SYSTEM IN SUPPORT PROGRAM TO ACHIEVE STRATEGIC VISION & MISSION IN OFFICE OF PUBLIC ACCOUNTANTS AND CONSULTANTS SERVICES - Ardian Pangasto; R. A. Gafar, Ir. R. A. Gafar, Ir. (Jurnal Sistem Informasi, 2003)
The concept and basic design of the training information system is made as one ofstrategic programs to achieve the vision and mission of public accounting andconsulting services and / or organization that evaluates human resource developmentis a strategic role in winning the competition. This system is designed specifically toprocess and monitor the development of human resource skills as a benchmark for thesuccess of the training. in addition to reducing the daily work in controlling theregistration participants training administration, training, update notices and othersecord.